Analysis of Switchable Spin Torque Oscillator for Microwave Assisted Magnetic Recording - Mingsheng Zhang; Tiejun Zhou; Zhimin Yuan (Advances in Condensed Matter Physics)
A switchable spin torque oscillator (STO) with a negative magnetic anisotropy oscillation layer for microwave assisted magnetic recording is analyzed theoretically and numerically. The equations for finding the STO frequency and oscillation angle are derived from Landau-Lifshitz-Gilbert (LLG) equation with the spin torque term in spherical coordinates. The theoretical analysis shows that the STO oscillating frequency remains the same and oscillation direction reverses after the switching of the magnetization of the spin polarization layer under applied alternative magnetic field. Numerical analysis based on the derived equations shows that the oscillation angle increases with the increase of the negative anisotropy energy density (absolute value) but decreases with the increase of spin current, the polarization of conduction electrons, the saturation magnetization, and the total applied magnetic field in the z direction. The STO frequency increases with the increase of spin current, the polarization of conduction electrons, and the negative anisotropy energy density (absolute value) but decreases with the increase of the saturation magnetization and the total applied magnetic field in the z direction.